The historical and archaeological significance of the Bohai cultural layers at the site of Utesnoe-4 - Kim, Alexander Alexeevich; Burdonov, Andrei Victorovich; Mezentsev, Alexander Leonidovich (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The site of Utesnoe-4 is located in the Primorye region, near the village of Utesnoe (district of Ussuriysk), in the southern part of the Russian Far East. It is a stratifi ed site with archaeological artefacts ranging from the Krounovka culture to the Jurchen period. More than 200 Bohai and Jurchen sites are located in the Primorye region; however, it is only at Utesnoe-4 that Mohe, Bohai and Jurchen artefacts are found on the same site and this provides the opportunity to analyse them in a different way. Despite the fact that Russian archaeologists have excavated Utesnoe-4 for only two fi eld seasons, materials from this site have the potential to contribute important information to the history and archaeology of the region. The aim of this article is to present the analysis of the assemblages from Utesnoe-4 and consider the historical signifi cance of this site and neighbouring areas. The article will be available as a PDF in the near future.